2011
DOI: 10.1007/s10681-011-0492-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Fusarium crown rot resistance of durum wheat by introgressing chromosome segments from hexaploid wheat

Abstract: Compared with hexaploid wheat, tetraploid durum is more susceptible to Fusarium crown rot (FCR) infection. The feasibility of enhancing FCR resistance in durum wheat by introgressing chromosome segments of hexaploid wheat was investigated by generating and analysing a backcross population derived from a susceptible durum wheat variety 'Bellaroi' (recurrent parent) and a resistant hexaploid genotype 'CSCR6' (donor parent). Together with a few scattered segments on various chromosomes, segments of a large sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…All of the Qld and seven of the 19 NSW sites were planted to bread wheat varieties. Hence, the widespread occurrence of FHB in 2010 does not indicate a clear association with durum wheat, which is more susceptible than bread wheat (Ma et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…All of the Qld and seven of the 19 NSW sites were planted to bread wheat varieties. Hence, the widespread occurrence of FHB in 2010 does not indicate a clear association with durum wheat, which is more susceptible than bread wheat (Ma et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the incorporation of FCR resistance from wild relatives into adapted varieties may require time, especially if linkages are found between the genes conditioning FCR resistance and undesirable traits. The transfer of FCR resistance from bread to durum wheat can be another option to improve the resistance of durum varieties, and preliminary reports suggest that such transfer is technically possible (Ma et al, 2012b;Martin et al, 2013).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…This also appeared to be the case for QTLs related to resistance to crown rot and Fusarium head blight. These major QTLs also failed to provide resistance to crown rot and Fusarium head blight once transferred to the durum background (Ma et al, 2012a; Xie GQ and Liu CJ, unpublished results). Previous studies (Ma et al, 2012a) have suggested that possible reasons for the loss of function of these genes may be due to the absence of Dchromosomes, which might be essential for the proper function of the genes, or alternatively, might be due to the presence of suppressor genes in the durum.…”
Section: Discussionmentioning
confidence: 96%
“…However, to our knowledge, only one study has been carried out in this area to date. A backcross population, which was developed by crossing durum wheat 'Bellaroi' and hexaploid wheat 'CSCR6', was used to investigate the possibility of improving disease resistance of durum wheat by introgressing the resistant genes from hexaploid into the durum genetic background (Ma et al, 2012a). The results indicated that 67% of the population lines showed better crown rot resistance than the recurrent durum parent 'Bellaroi'.…”
Section: Introductionmentioning
confidence: 99%